2020
DOI: 10.1111/dth.13443
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of pregnancy associated plasma protein‐A and neopterin levels in Behçet's patients

Abstract: Behçet's disease (BD) is an autoimmune disease that affects many organs. We aimed to investigate the relationship between BD and these pregnancy‐associated plasma protein A (PAPP‐A), neopterin, and high sensitive C‐reactive protein (hsCRP) parameters. The study included 57 BD patients and 54 healthy controls. After evaluating the active and inactive disease status of the patients, analyzes were performed. When comparing the patient and control groups, neopterin (111.27 ± 37.49; 76.77 ± 38.27 [nmol/L]; P < .001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Thirty studies (34 study groups) reported serum or plasma neopterin concentrations in a total of 2,618 RD patients (mean age 43 years, 32% males) and 5,318 healthy controls (mean age 42 years, 47% males) ( 55 , 59 , 61 , 64 67 , 69 – 87 , 89 , 90 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty studies (34 study groups) reported serum or plasma neopterin concentrations in a total of 2,618 RD patients (mean age 43 years, 32% males) and 5,318 healthy controls (mean age 42 years, 47% males) ( 55 , 59 , 61 , 64 67 , 69 – 87 , 89 , 90 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies were conducted in Asia ( 55 , 59 , 65 , 66 , 69 , 70 , 72 74 , 77 , 78 , 80 82 , 84 89 ), six in Europe ( 61 , 62 , 64 , 67 , 79 , 90 ), three in Africa ( 71 , 75 , 83 ), and the remaining one in America ( 76 ). Ten study groups included patients with RA ( 55 , 76 , 78 81 , 83 , 86 , 89 , 90 ), nine with SLE ( 55 , 65 , 70 , 71 , 75 77 , 82 , 84 ), eight with BD ( 59 , 65 , 66 , 69 , 72 74 , 87 ), three with IIM ( 62 , 88 ), two with pSS ( 64 , 67 ), one with SSc ( 61 ), and one with AS ( 85 ). The analytical methods used for measuring neopterin included an enzyme-linked immunosorbent assay (ELISA) in 18 studies ( 61 , 64 67 , 69 – 71 , 74 76 , 78 , 79 , 81 , 85 , 86 ,...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell-mediated immunity is also activated in various neurological, cardiovascular, infectious, autoimmune diseases, and malignancies, proving this marker’s increased levels [ 30 ]. Previous studies found NPT increases in the body fluids of patients such as polycystic ovary syndrome, RA, SpA, diabetes mellitus, SLE, multiple sclerosis, celiac disease, and IBD [ 31 34 ]. Elevated urinary or serum NPT levels suggest a poor prognosis in cancer patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%